Firm Performance During The COVID-19 Outbreak in Sri Lanka: Empirical Evidence - Tharsika, K.; Sayanthan, B.; Pratheepkanth, P. (4th Research Conference on Business Studies (RCBS) - 2022 (p. 11). Vavuniya : University of Vavuniya, Sri Lanka., 2022)
The advanced shock of the COVID-19 pandemic heightened a massive uncertainly shock. It led to a significant increase in healthcare spending, which obviously impacted economic growth and firm growth. However, the impact of the COVID pandemic on financial performance has been mixed. As a result, the question of how much companies' financial performance has changed due to the COVID pandemic has yet to be empirically answered. The study's aim is to see if the financial performance of listed companies in Sri Lanka has changed due to the COVID-19 pandemic. This study uses both quantitative and secondary data collection methods. The initial sample includes all 296 companies listed on the CSE in Sri Lank. After excluding financial firms, which have different financial practices than non-financial firms, firms with fiscal years ending on December 31st, and firms that did not publish their annual report when this study was conducted, the final sample consists of 176 companies. In this study, the descriptive statistic, Kolmogorov-Smirnova test, Shapiro-wilk test, and Wilcoxon signed-rank test are used to try to solve that puzzle. According to the study, the financial performance of listed companies in Sri Lanka has not changed significantly due to the Novel Coronavirus pandemic.
Keywords: COVID-19; Firm performance; Kolmogorov-Smirnova test; Shapiro-wilk test; Wilcoxon signed-rank test